TRANSFORMATION OF THE EMPLOYMENT STRUCTURE IN COUNTRIES OF THE WORLD UNDER THE INFLUENCE OF DIGITIZATION AND HIGH-TECHNOLOGICAL DEVELOPMENT (INNOVATIVE ECONOMY, 2025)
Smіesova V.L., Bohdanov O.O.  TRANSFORMATION OF THE EMPLOYMENT STRUCTURE IN COUNTRIES OF THE WORLD UNDER THE INFLUENCE OF DIGITIZATION AND HIGH-TECHNOLOGICAL DEVELOPMENTPurpose. The aim of the article is to substantiate the main consequences of the transformation of the employment structure in countries around the world in the context of modern geo-economic and geopolitical shifts, to identify the risks of a decline in employment and the prospects for its increase in the process of digitalization and high-tech development.Methodology of research. Methods of scientific abstraction and systematization were used to analyse the consequences of labour market changes and prospects for increasing employment levels based on digitalization; induction and deduction were used to substantiate the risks of declining employment caused by digital changes at the national level and in the global environment; analysis and synthesis were used to study the impact of contemporary geo-economic and geopolitical challenges on the transformation of the employment structure and the prospects for increasing it through the use of digital technologies; economic and statistical analysis – to substantiating the effects of using digital technologies in the process of production and sales of products to achieve high-tech development and increase labour productivity.Findings. The consequences of the impact of modern geo-economic and geopolitical factors and challenges on the main macroeconomic indicators and employment structure of countries around the world are substantiated. Prospects for increasing the level of employment in the global labour market in the context of digitalization and high-tech development are identified. The current state and trends in the development of the labour market in the global economy are analysed, and the advantages of using digital technologies and artificial intelligence by employees in the process of labour activity are substantiated. A comparison of changes in the structure of employment in developed and developing countries in the process of digitalization is carried out. The main risks of a decline in employment caused by digital changes at the national and global levels are substantiated. Proposals and recommendations are provided in the field of state regulation to prevent the distortion of the employment structure under the influence of digital transformations and to reap the benefits of the digitalization of the economy, business, and society.Originality. The systematization of the impact of modern geo-economic and geopolitical challenges on the structure of employment in the context of digitalization and high-tech development has been further developed. An approach to the formation of public policy directions has been proposed with the aim of preventing a decline in employment and leveling out potential negative changes in its structure at the national level.Practical value. The practical significance lies in the development of practical recommendations for shaping the state's economic policy in terms of expanding the use of digital technologies in the economy and business, increasing employment, improving skills, and expanding digital infrastructure.Key words: employment, labour market, digitalization, high-tech development, artificial intelligence, business digitalization, digital technologies.
Keywords: employment; labour market; digitalization; high-tech development; artificial intelligence; business digitalization; digital technologies